The effect of expatriate salary on host country nationals in South Africa : a study involving perceived compensation disparity, organisational commitment and job satisfaction - Barkhuizen, E. Nicolene (University of Pretoria, 2013)
Dissertation (MCom)--University of Pretoria, 2012.